Superior Capsular Reconstruction for Massive Rotator Cuff Tears: A Critical Analysis Review. Issue 6 (June 2019) - Galvin, Joseph W.; Kenney, Raymond; Curry, Emily J.; Parada, Stephen A.; Eichinger, Josef K.; Voloshin, Ilya; Li, Xinning
Abstract : A massive rotator cuff tear is defined as a tear involving >2 tendons or >5 cm of retraction. Superior capsular reconstruction is done with either a folded fascia lata autograft (6 to 8 mm in thickness) or acellular dermal allograft (3 to 4 mm in thickness). The graft is secured arthroscopically with anchors on the superior glenoid rim and multiple anchors on the humeral head with use of a transosseous-equivalent repair technique. Superior capsular reconstruction is indicated for younger patients with massive and irreparable rotator cuff tears involving the supraspinatus and infraspinatus with minimal arthritis, intact subscapularis, and a functional deltoid. Contraindications include bone defects, stiffness, and moderate to severe arthropathy. Arthroscopic superior capsular reconstruction with fascia lata autograft or humeral dermal allograft is a surgical option, with multiple studies showing statistically significant improvement in short-term outcomes for both pain and function among younger patients with massive irreparable rotator cuff tears. The long-term clinical effectiveness and value have yet to be determined. Biomechanical data suggest improved restoration of superior glenohumeral stability with decreased subacromial contact pressures in association with the use of the 8-mm fascia lata graft as compared with the 4-mm acellular humeral dermal allograft. In addition, fascia lata graft has shown less elongation and thinning than humeral dermal graft. Either fascia lata autograft or humeral dermal allograft may be used clinically for arthroscopic superior capsular reconstruction; however, a graft thickness of at least 3 mm is recommended to decrease the risk of radiographic and clinical failure. No comprehensive quality-of-life or cost-comparison analyses are available to compare superior capsular reconstruction, reverse total shoulder arthroplasty (rTSA), tendon transfer, and partial rotator cuff repair for the treatment of massive irreparable rotator cuff tears. However, the potential higher cost of superior capsular reconstruction and the lack of long-term clinical outcomes or revision data suggest that either an attempt at repair or primary arthroplasty may be more cost-effective than superior capsular reconstruction. Long-term outcome data are essential to determine the role of superior capsular reconstruction for young patients with massive irreparable rotator cuff tears. Superior capsular reconstruction using fascia lata autograft may provide a different biomechanical and biological healing environment compared to acellular dermal allograft. Thus, the clinical outcome data between the 2 graft methods should not be generalized.